2010
DOI: 10.1017/s1049096510000168
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Women in Publication: An Analysis of Political Communication and the International Journal of Press/Politics

Abstract: Scholarly publication in peer-reviewed journals is widely regarded as the road to scholarly success. However, in a diversity of fields such as sociology, economics, and political science, it has been shown that the rate of publication is much lower for women than for men. The question of whether a systematic relationship exists between gender and research methods has also frequently been debated. In this paper, we explore patterns of authorship and scholarship in two influential interdisciplinary journals, Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…A few of the female lead authors had more than five publications during this time. Comparing these rates to the authorship rates in Evans and Bucy's (2010) study of the subfield of political communication, we find a significantly higher percentage of repeat author publications within these top political science journals. While some female scholars publish frequently in these top journals, they do not dominate them, which is a positive sign for gender representation in publication.…”
Section: Discussionmentioning
confidence: 72%
“…A few of the female lead authors had more than five publications during this time. Comparing these rates to the authorship rates in Evans and Bucy's (2010) study of the subfield of political communication, we find a significantly higher percentage of repeat author publications within these top political science journals. While some female scholars publish frequently in these top journals, they do not dominate them, which is a positive sign for gender representation in publication.…”
Section: Discussionmentioning
confidence: 72%
“…Numerous studies have found that women publish fewer articles and books than their male colleagues. Kyvik (1990) reports that "virtually all studies that have examined scientific publishing among men and women scientists have found that men are more productive than women" (see also Cole and Zuckerman 1984;Fish and Gibbons 1989;Bellas and Toutkoushian 1999;Sax, Hagedorn, Arredondo, and Dicrisi 2002;Taylor, Fender, and Burke 2006;Evans and Bucy 2010). While recent research suggests that women may be catching up and, in some disciplines, may have similar publication rates as their male colleagues, many reports continue to show that women have lower productivity in most academic fields (Abramo, D'Angelo, and Caprasecca 2009;Hesli and Lee 2011).…”
Section: Women Scholarly Productivity and Tenurementioning
confidence: 99%
“…This underrepresentation is not limited to higher education administration; rather, it crosses multiple venues. With specific regard to women, researchers have noted a gender gap in academic publishing, both generally (Leahy, 2006;Ward & Grant, 1996) and within specific disciplines or fields, including counselor education (Buffalino Roland, & FontanesiSeime, 1996), ecology (Martin, 2012), geography (Rigg, McCarragher, & Krmenec, 2012) leisure studies (Aitchison, 2001), library science (Terry, 1996), physical therapy (Kaufman & Chevan, 2011), political science (Evans & Bucy, 2010;Mathews & Anderson, 2001), and medicine (Barnett et al, 1998, Jagsi et al, 2006.…”
Section: Introductionmentioning
confidence: 99%